Ultrasound velocities and elastic properties of LICL doped zinc –borate glasses - Vijayatha, D.; Chandrashekaraiah, G.; Viswanatha, R.; Narayana Reddy, C. (International Journal of Engineering and Technology, 2018)
Sound velocities and elastic property measurements have been employed to study the strength and rigidity of the structure of ZnO-B2O3 glasses doped with LiCl. Moduli of elasticity such as longitudinal, Young`s , bulk and shear modulus have been calculated using ultra sound velocities such as longitudinal and transverse velocities are measured at a frequency of 10 MHz as function of LiCl concentration. Both sound velocities and elastic moduli decrease with increase of LiCl concentration. The results are discussed in the view of borate network and dual structural role played by the divalent zinc ions present in the network. The results indicate that the Zn+2 ions are likely to occupy network forming positions in this glass system. While LiCl is a typically dissolved in the borate network and Cl- occupy the interstitial positions.Â